Usage of Games in the Development of Cognitive Processes of Preschool Children (Eurasian Journal of Learning and Academic Teaching, 2023)
This article discusses the development of cognitive processes of preschool children, play activities, influence on education and upbringing processes, their physical and mental development through play activities, pedagogical-psychological analysis and necessary information.